P64 NIMBUS geometric clot extractor for tough clots: SPERO study results and clot composition. (29th August 2022) - van den Berg, R; Ribó, M; Arnberg, F; Estrade, L; Thornton, J; Tomasello Weitz, A; Gontu, V; Karam, A; Hernández, D; Clarençon, F; Buhk, J-H; Wiesmann, M; et al.
Abstract : Introduction: The NIMBUS Geometric Clot Extractor was specifically developed for fibrin rich tough clots which are considered challenging to remove using standard mechanical thrombectomy (MT) techniques. Study aim: The SPERO Study (NCT03898960, Cerenovus) aimed to evaluate the use of NIMBUS in patients with challenging clots and analyse the composition of retrieved thrombus. Methods: Fifty-four subjects were enrolled at 11 European centres between October 2019 and February 2022. Use of NIMBUS was permitted after 1 or 2 MT attempts failed to achieve substantial reperfusion mTICI≥2b, regardless of whether or not clot material was retrieved. Any MT technique allowed after 3 NIMBUS passes. Clot from 27 cases was analysed by blinded central labs. Key clot composition findings are presented below; full results, including the primary endpoint (core lab adjudicated eTICI≥2b after last NIMBUS pass) will be presented at the conference, following database lock in June 2022. Results: Mean age was 71.9±14.09yrs, with mean time since onset of 8.4±5.32hrs (median 6.3); 24.1% subjects received IV-tPA. NIMBUS was used after an average of 1.8 failed MT passes (22.2% and 77.8% after 1 and 2 passes, respectively). Composition analysis revealed 44.9±25.7% RBC and 33.6±16.9% fibrin in first procedural pass (non-NIMBUS) vs 27.4±19.1% RBC and 42.0±16.2% fibrin for clot retrieved with the first pass of NIMBUS. Conclusions: In challenging cases with tough clot, first pass of NIMBUS retrieved clot richer in fibrin and lower in RBC content than clot retrieved with the first pass of standard MT devices. References: Fennell VS, Setlur Nagesh SV, Meess KM, Gutierrez L, James RH, Springer ME, Siddiqui AH. What to Do about Fibrin Rich 'Tough Clots'? Comparing the Solitaire Stent Retriever with a Novel Geometric Clot Extractor in an in vitro Stroke Model. J Neurointerv Surg 2018 Sep;10 (9):907–910. DOI: 10.1136/Neurintsurg-2017-013507. EPUB 2018 Jan 19. PMID: 29352061. Do you have any conflict of interest to declare? : Yes Conflict of Interest Statement: DL – consultant: Genentech, Cerenovus, Medtronic, Stryker. FA – grants from Stryker, Cerenovus. FC – personal fees: Balt, Stryker, Artedrone. HD – research support: French Ministry of Health, Genavie Foundation, Société Française de Radiologie, Société Fraçaise de Neuroradiologie. JHB – consultant fees: Microvention, Stryker, Cerenovus, Acandis, Medtronic. JT – consultant, stock: MicroVention. KD – holdings: Perfuze; research funding: Science Foundation Ireland that is cofunded by Cerenovus. MR – equity/advisory board: Methinks Software; cofounder: Anaconda Biomed; consultant: Methinks, Medtronic, Cerenovus, Apta Targets, Anaconda Biomed, Stryker, Johnson and Johnson, Perflow Medical, Sanofi, Rapid AI, Philips; grants: CVAid. MW – funding: Stryker Neurovascular, Bracco Imaging, Medtronic, Penumbra, Siemens Healthcare, Abbott, AB Medica, Acandis, Asahi Intecc, Bayer, B. Braun, Cerenovus, Codman Neurovascular, Dahlhausen, Kaneka Pharmaceuticals, Mentice AB, Microvention, Penumbra, Phenox, Philips Healthcare, Route 92, SilkRoad Medical, St. Jude. RvdB – support: Cerenovus; consultant: Johnson and Johnson Health Care Systems; grant support: Netherlands Organisation for Health Research and Development. TA – consultant: Neuravi/Cerenovus, Ablynx, Amnis Therapeutics, Medtronic, Rapid Medical, Stryker; honoraria: Anaconda, Cerenovus, Stryker, and for serving on the DSMB for the Excellent Registry, SPERO and Solonda studies; shareholder: Rapid Medical, Ceroflo.